2015
DOI: 10.1002/ejhf.256
|View full text |Cite
|
Sign up to set email alerts
|

Impact of surgical ventricular reconstruction on sphericity index in patients with ischaemic cardiomyopathy: follow‐up from the STICH trial

Abstract: Aims We sought to evaluate associations between baseline sphericity index (SI) and clinical outcome, and changes in SI after coronary artery bypass graft surgery (CABG) with or without surgical ventricular reconstruction (SVR) in ischemic cardiomyopathy patients enrolled in the SVR study (Hypothesis 2) of the Surgical Treatment for Ischemic Heart Failure (STICH) trial. Methods and results Among 1,000 patients in the STICH SVR study, we evaluated 546 patients (255 randomized to CABG alone and 291 to CABG+SVR)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 23 publications
1
12
2
Order By: Relevance
“…Amongst markers of advanced LV remodeling, diastolic dysfunction may be more important prognostic marker than abnormal LV geometry. We previously demonstrated that increased LVESVI and sphericity index influences poor survival following CABG or CABG+SVR (4,25), but in our current analysis, diastolic function outperformed sphericity index. Whereas previous HFrEF studies have identified deceleration time, E/e' ratio or diastolic function grade as prognostic diastolic function variables (5, 6), we found that E/A ratio was the most robust indicator in HFrEF due to ischemic etiology.…”
Section: Discussioncontrasting
confidence: 65%
“…Amongst markers of advanced LV remodeling, diastolic dysfunction may be more important prognostic marker than abnormal LV geometry. We previously demonstrated that increased LVESVI and sphericity index influences poor survival following CABG or CABG+SVR (4,25), but in our current analysis, diastolic function outperformed sphericity index. Whereas previous HFrEF studies have identified deceleration time, E/e' ratio or diastolic function grade as prognostic diastolic function variables (5, 6), we found that E/A ratio was the most robust indicator in HFrEF due to ischemic etiology.…”
Section: Discussioncontrasting
confidence: 65%
“…Alterations of the geometric shape of the left and right ventricles have been reported in adult and pediatric patients as markers of cardiac dysfunction in which the ventricle appears to be flattened or rounded, depending on the underlying abnormality . One method used for evaluation of ventricular shape involves measuring the end‐diastolic BAL and TL for the right and left ventricular chambers and computing the GSI using either BAL/TL or TL/BAL (Figure ) …”
Section: Discussionmentioning
confidence: 99%
“…Alterations of the geometric shape of the left and right ventricles have been reported in adult and pediatric patients as markers of cardiac dysfunction in which the ventricle appears to be flattened or rounded, depending on the underlying abnormality. [21][22][23][24][25][26][27][28][29][30][31][32][33][34] One method used for evaluation of ventricular shape involves measuring the end-diastolic BAL and TL for the right and left ventricular chambers and computing the GSI using either BAL/TL or TL/BAL (Figure 4). 8,21,35 Once an abnormal GSI was identified, the only group that showed a significant increase in the TL, thus leading to a more globular-shaped heart, was the group of fetuses with cardiac dysfunction (Table 5), which was similar in fetuses with an estimated fetal weight below the 10th centile (27.7%) and above the 10th centile (29.5%).…”
Section: Discussionmentioning
confidence: 99%
“…The sphericity index (SI) is used to evaluate the shape of the right and left ventricles of the heart and is derived by calculating the ratio between the end-diastolic mid-basal-apical and transverse lengths (Figure 1a). SI has been examined in adult and pediatric patients and found to be a useful tool to detect abnormal cardiac function resulting from remodeling of the ventricular chamber [1][2][3][4][5][6][7][8][9][10][11][12][13] . Only six studies have evaluated the SI of the fetal heart [14][15][16][17][18][19] .…”
Section: Introductionmentioning
confidence: 99%